The myths of Prometheus and the Black Sea region: conflicting versions, shifting paradigms (Colloquia Comparativa Litterarum, 2025)
The topic of the paper is the interrelation between two ideological constructs: the figure of Prometheus and the so-called Black Sea region. Both of them represent, in specifically transformed versions, primary ideas and realities that lack the additionally attributed coherence of the later concepts currently in use. It aims to explore the key ancient myth of Prometheus in comparative perspective, juxtaposing the stable presence it retains in the Western cultural imagination with its life in the Black Sea region, where this myth initially emerged. It focuses specifically on the underestimated political mobilization of the Prometheus myth in the construction of national identities and in the manufacturing of various ideologies. The different, often conflicting versions are analysed in diachronic perspective that provides observability of the potential paradigm shifts in the conceptualizations of the Prometheus figure.
Keywords: Prometheus; Black Sea region; national identities; political mobilization